Gender‐typing of leadership: Evaluations of real and ideal managers. Issue 2 (5th January 2015) - Cuadrado, Isabel; García‐Ael, Cristina; Molero, Fernando
<x xml:space="preserve">Abstract</x> This research focuses on female underrepresentation in managerial positions. Specifically, two studies examine gender‐typing for managerial roles in Spain using ratings for real and ideal managers. In addition, we analyse the existence of same‐gender bias on evaluations of the behavior of actual leaders. In the first study, 195 Spanish workers evaluate the extent to which gender‐stereotypical traits are important for becoming a successful middle manager in three conditions (female managers, male managers, and managers in general). In the second study, we explore the degree to which the behavior of real Spanish managers is gender‐typed and the existence of same‐gender bias on leadership styles – transformational, transactional and avoidant/passive – and on leadership outcomes – effectiveness, extra effort and satisfaction – from the perspective of subordinates (N = 605). Overall, the results demonstrate that masculine characteristics were rated as more important than feminine characteristics for managerial positions, and they were more often assigned to male managers than to female managers. Unexpectedly, this manager‐male association is stronger among female participants than among male participants. Our findings also demonstrate that women subordinates evaluate their same‐sex supervisors more favorably in transformational leadership, effectiveness, and extra effort. The negative consequences derived from gender‐typing managerial positions are highlighted according to the role congruity theory of prejudice toward female leaders. The positive effects of in‐group female bias on behavior ratings are also noted. The mixed implications of these results for women's advancement to leadership positions are discussed.